Long-Term Seed Dormancy in Poa Pratensis L. Northern Norway - Aamlid, Trygve S; Arntzen, Dagfinn (UKnowledge, 2024)
Inadequate gennination has often been obseived when planting Poa pratensis L. cv. Lavang (69°N) in northern Norwegian grasslands. This investigation was intended to elucidate whether this was due lo longterm seed dormancy, Seed-lots grown in different years in northern and southern Norway and stored at O-to•c, were germinated in Jakobsentype germinators al various combinations of temperature and light. Significant dormancy was expressed at 21 °C even after 10 years of storage. Al this constant temperature, germination was promoted by 8 h fluorescent light compared with darkness and continuous light. Al 21/ I 2°C alternating temperature, seed genninated well irrespective of light condition. No consistent relationship was found between seed donnancy and place of production, temperature during seed maturation or seed weight. Pre-chilling of imbibed seed for 32 days at O.S°C or O.S/3.O°C decreased subsequent gennination at 12/6 and 18/12°C, but not at 21/ 12°C. II is concluded that long-term donnancy in Lavang may contribute to poor field germination, especially when diurnal fluctuations in temperature and light are small.